Warfare and society in British India, 1757-1947
1 online resource (x, 265 pages).
Keywords: "This book explores the intricate and intimate relationship between military organization, imperial policy, and society in colonial South Asia. The essays in the volume focus on technology, logistics and state building, highlight the salient features of expansion and consolidation of imperial control over the subcontinent, and ultimate demise of the Raj. Further, it turns the spotlight on to subaltern challenges to imperialism as well as the role of non-combatants in warfare. The volume: - Deals with both conventional and guerrilla conflicts and focuses on the frontiers (both North-West and North-East, including Burma); - Looks at the army as an institution rather than present a chronological account of military operations, which highlights the complex and tortuous relationship between combat institution, colonial state, and Indian society; - Integrates top-down approaches in military and strategic studies with the bottom-up perspectives and discusses on how the conduct of war (organization and technology) is related to the economic, societal and cultural impact of war. A rich account of the British 'Army in India', this book will be essential reading for scholars and researchers of South Asian history, military history, political history, colonialism and the British Empire"--